2014
DOI: 10.2489/jswc.69.5.449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of straw incorporation on soil moisture, evapotranspiration, and rainfall-use efficiency of maize under dryland farming

Abstract: Field experiments were conducted from 2008 to 2010 in the Weibei Highlands of China to study the effects of straw incorporation on soil moisture, evapotranspiration (ET), and rainfall-use efficiency (RUE) of maize (Zea mays L.) under semiarid conditions in dark loessial soil. The straw application rates were at low straw ([LS] 4.5 t ha -1 ), medium straw ([MS] 9 t ha -1 ), and high straw ([HS] 13.5 t ha -1 ) rates combined with fixed levels of chemical fertilizers compared with only chemical fertilizers. Straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
3
12
0
1
Order By: Relevance
“…Daily E differences between the two sites were a good indicator of how the different soil conditions affect the direct water losses from the soil surfaces. Similar to the previous studies, we found that during the oMGS rainfall events, the simulated E was suppressed by the residue cover layer at the no-till site compared to the bare and disturbed soils at the conventional tillage site (Salado-Navarro and Sinclair, 2009;van Donk and Klocke, 2012;Wang et al, 2014). This amount of reduced E at CAF-NT was mostly affected by rainfall frequency rather than rainfall amounts, which was also supported by van Donk et al (2010) where they found the different magnitude in E between residue-covered and bare soils increased during the infrequent and light rainfall events.…”
Section: Tillage Practice Effects On Annual Cropping Areasupporting
confidence: 89%
“…Daily E differences between the two sites were a good indicator of how the different soil conditions affect the direct water losses from the soil surfaces. Similar to the previous studies, we found that during the oMGS rainfall events, the simulated E was suppressed by the residue cover layer at the no-till site compared to the bare and disturbed soils at the conventional tillage site (Salado-Navarro and Sinclair, 2009;van Donk and Klocke, 2012;Wang et al, 2014). This amount of reduced E at CAF-NT was mostly affected by rainfall frequency rather than rainfall amounts, which was also supported by van Donk et al (2010) where they found the different magnitude in E between residue-covered and bare soils increased during the infrequent and light rainfall events.…”
Section: Tillage Practice Effects On Annual Cropping Areasupporting
confidence: 89%
“…Soil fertility properties, including soil total nitrogen (N), total P and SOC (soil organic carbon), were measured according to (Wang, Jia, & Liang, ).…”
Section: Methodsmentioning
confidence: 99%
“…The available Fe, Zn and Mn concentrations were determined by microwave digestion-inductively coupled plasma emission spectrometry ICP-AES (ICP6300; Thermo Scientific) described by Li, Coles, Ramsey, and Thornton (1995). Soil fertility properties, including soil total nitrogen (N), total P and SOC (soil organic carbon), were measured according to (Wang, Jia, & Liang, 2014).…”
Section: Soil Physicochemical Properties Analysismentioning
confidence: 99%
“…One way to use saline soils and water in desert area is to identify and use salt and drought tolerant plants [1] [2] [3] [4] [5]. Another strategy is use of hydrogels.…”
Section: Introductionmentioning
confidence: 99%